Psychometric Properties of the Persian Version of a Drug Use Temptation Scale - Yousef Asli Khalan; Masoud Karimi; Abdolrahim Asadollahi; Mohammad Hossein Kaveh (Shiraz University of Medical Sciences, 2020)
Introduction: One of the main challenges of Methadone Maintenance treatment (MMT) centers is the patients' non-adherence to treatment process in tempting situations. This study was conducted to validate the Persian version of one of the valid questionnaires on situational drug use temptation. Methods: A cross‑sectional study was carried out on 150 men referring to MMT centers in Shiraz, Iran, in 2019. Data were collected using a self-administered questionnaire containing demographic data and Persian version of drug use temptation questionnaire with 20 items. The content validity was assessed by 15 psychiatrists and health education and promotion experts based on the Lawshe criteria. The reliability of the questionnaire was determined using Cronbach's alpha. The construct validity was evaluated by exploratory Principal Component Analysis (PCA) and confirmatory factor analysis. Data were analyzed using SPSS 24 and Amos 24. Results:  Overall, 141 individuals completed the questionnaire (response rate: 94%). The mean and standard deviation of the participants' age were 37±7. The Kaiser-Meyer-Olkin test of sampling was adequate (KMO 0.913) and the Bartlett test of sphericity was significant (Chi-square 1847.65; p= 0.001). Four factors were extracted and two items were not included in any of the factors. Goodness of fit indices of structural equation model, i.e. Chi2, Chi2/df, and RMSEA were ​​ 158.504, 1.22 and 0.04, respectively, which indicated the acceptable fitness of the model. Conclusion: The Persian version of the questionnaire of temptation to use drugs is suitable for use among the Iranian population.